IMPROVEMENT OF ARGUMENTATIVE WRITING SKILLS THROUGH THE COOPERATIVE INTEGRATED READING AND COMPOSITION METHOD (CLASS X ACTION RESEARCH AT SMAN 7 TANGERANG CITY) - Zahroh Nurhillal (RADJA PUBLIKA, 2025)
This research aims to improve the argumentative writing skills of 10th-grade students at SMAN 7 Kota Tangerang through the application of the Cooperative Integrated Reading and Composition method. This method involves collaborative learning in small groups consisting of four heterogeneous members, allowing students to discuss and develop the themes they will write about. This research was conducted in two cycles, with data collection through observation, questionnaires, and analysis of students' written work. The research results show that before the implementation of the method, only 19.35% of students achieved the Minimum Completeness Criteria (KKM) with an average score of 66.03. After the implementation of the method, in cycle I, 61.29% of students reached the Minimum Completeness Criteria (KKM), and in cycle II, the average student score increased to 78.39 with 77.42% of students reaching the KKM. These findings indicate that the Cooperative Integrated Reading and Composition method is effective in improving students' argumentative writing skills, although there are still challenges in distinguishing between argumentation and opinion. This study recommends strengthening teaching methods and increasing time for writing practice so that all students can achieve optimal results.